Childhood obesity. (March 2019) - Lanigan, Julie; Tee, Louise; Brandreth, Rachael
Abstract: Childhood obesity is a serious global health problem. It begins early in life during the preschool years, and, for many, the obesity is carried forward into later childhood and adult life. Once established, obesity is difficult to reverse and is associated with poorer health outcomes in the short and long term. Tackling obesity in childhood is important to reduce life-long risk and protect health. However, service provision is lacking in the UK and other countries. Interventions that are successful in the prevention and management of childhood obesity are urgently needed. These should ideally be evidence-based and target the youngest children and their families. Multicomponent lifestyle programmes and strategies can be effective in reducing childhood obesity. For greatest success, these should be tailored to individual family needs.